PENINGKATAN KUALITASGURU SMU MELALUI PROGRAM PGSMU - Das Salirawati Das Salirawati (LPMPP Universitas Negeri Yogyakarta, 2000)
The teaches have an itnportant role 0 determinethe qualityof education general and of teachinglearning in particular. As hUlnan Ressources ini theaduc.ation sector, the teachers are demanded 0 developang to increse their quaity that related to their teaching-quality as well as their knowladge quality. This isrelevant to their profesion that have to follow the eradevelopment.Senior Secondary School Teacher Education(SSSTE) has been issued' by governlnent through theGovernment Regulation No. 30, 1990 However, manyparticipantsof the SSSTE however program justappear in the academic year 1999/2000 indicated bythe factthat many SMU teachers undertake this program in certainuniversttles such as the StateUniversityofYogyakarta. This progranl is organizedwith the aimti j'hcrease the quality of SMlJ teacherswho have tacher's cetificate of D3 to become S IDegree.It is expected that the improvement theteacher's quality as HUlnan Resources in the educationsector canbe achieved through the SSSTE prograln;The study ternl of SSSTE f01' about 10 1110unths isenough to give. the enrichlnent Inaterial and to broadenthe conceptof the students. Novertheless the successof the SSSTE progranl to inlprove teacher's quality ofSMU depands on the teaacher own efforts in study.Teachers motivationand awareness about theirresponsibility ii improve education quality inIndonesia is the key ofsuccess ofthe sssrrE prograln",